A Jewish Archaeology : The Christian Discovery of Jewish Catacombs in Rome - Russo, Jessica Dello (Jews, Judaism, and the Arts, 2025)
This study examines how various catacomb networks in Rome were eliminated and subsequently restored to the historical record as specifically Jewish sites. By exploring the evolution, interpretation and presentation of these catacombs from ancient times to the present, it offers fresh insights into their historical significance and the impact they have had on later generations. Understanding how this situation relates to the broader context of archaeological activity in Rome also highlights important changes in the study of catacombs during the nineteenth century that led to the identification of additional Jewish catacombs and other material evidence of Jews in Ancient Rome.